1997
DOI: 10.1016/s0895-7061(97)00211-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Blacks

Abstract: The excess of hypertension among blacks has been recognized since early in this century and explains a substantial portion of the black health disadvantage. In a cohort study begun in the 1970s, hypertension accounted for 20% of all-cause mortality among blacks, compared to 10% among whites. National data on trends in hypertension (140/90 mm Hg or treatment) prevalence from 1960 to 1990 suggest a decline from 44% to 32%, although differences in survey technique likely account for this pattern. During this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
1
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 43 publications
8
115
1
5
Order By: Relevance
“…In particular, this gradient was observed in black communities across Western Africa, the Caribbean Islands and the United States 6,7 to such an extent that, in the latter country, hypertension has been found to be more widespread among black people than among white people. 8 These observations have raised the possibility that the populations of developing countries, or at least those of African origin, have a higher susceptibility of blood pressure (BP) to excessive adiposity than Western populations and will be more severely affected, particularly in terms of hypertension-driven cardiovascular morbidity and mortality, by the current global upward trend in obesity. 9,10 This assumption has to be tested against the background of existing knowledge about the hypertensive effect of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this gradient was observed in black communities across Western Africa, the Caribbean Islands and the United States 6,7 to such an extent that, in the latter country, hypertension has been found to be more widespread among black people than among white people. 8 These observations have raised the possibility that the populations of developing countries, or at least those of African origin, have a higher susceptibility of blood pressure (BP) to excessive adiposity than Western populations and will be more severely affected, particularly in terms of hypertension-driven cardiovascular morbidity and mortality, by the current global upward trend in obesity. 9,10 This assumption has to be tested against the background of existing knowledge about the hypertensive effect of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These differences in the development and progression of hypertension in blacks have been proposed to be related to abnormal hemodynamic reactivity characterized by increased peripheral vascular resistance and diminished vasodilatation in response to environmental stress. 3 In a previous study, we found that plasma levels of the potent vasoconstrictor endothelin (ET)-1 were significantly higher in a black hypertensive group than in white hypertensive and white and black normotensive groups.…”
mentioning
confidence: 99%
“…[1][2][3][4] Furthermore, the disease onset is earlier, and the consequences of hypertension, which include heart failure, myocardial infarction, stroke, and renal failure, are more pronounced in black patients. 1,5 These racial differences in the development and clinical course of hypertension have been attributed to environmental and physiological factors.…”
mentioning
confidence: 99%